Vascular anomalies of orofacial region- a review - Pinto, Melisha Rolita; Kini, Raghavendra; John, Anuja; Nambiar, Arjun (Journal of Orofacial Research, 2019)
Vascular anomalies well-known as birthmarks are benign lesions of blood vessels or vascular elements are often considered errors of vascular morphogenesis. Numerous terms have been used to describe vascular anomalies on the basis of physical appearances leading to misdiagnosis followed by complications in the management of the lesion. Lack of complete understanding of the anomaly result in misdiagnosis. Main aim of this paper is to discuss the vascular anomalies of the head and neck region in detail which will enable the dental practitioner to arrive at a better diagnosis.